Continuous Delivery with Visual Studio ALM 2015 - Olausson, Mathias; Ehn, Jakob (Apress : Imprint: Apress, 2015)
This book is the authoritative source on implementing Continuous Delivery practices using Microsoft's Visual Studio and TFS 2015. Microsoft MVP authors Mathias Olausson and Jakob Ehn translate the theory behind this methodology and show step by step how to implement Continuous Delivery in a real world environment. Building good software is challenging. Building high-quality software on a tight schedule can be close to impossible. Continuous Delivery is an agile and iterative technique that enables developers to deliver solid, working software in every iteration. Continuous delivery practices help IT organizations reduce risk and potentially become as nimble, agile, and innovative as startups. In this book, you'll learn: What Continuous Delivery is and how to use it to create better software more efficiently using Visual Studio 2015 How to use Team Foundation Server 2015 and Visual Studio Online to plan, design, and implement powerful and reliable deployment pipelines Detailed step-by-step instructions for implementing Continuous Delivery on a real project.